Clinical application of high-speed turbine combined with pneumatic tooth elevator on mandibular impacted third molar extraction - MI Dawei; ZHOU Bi; PENG Bo; YAN Xu (Kouqiang hemian waike zazhi)
[Objective:] To explore the application effect of a minimally invasive tooth extraction tool in the treatment of mandibular impacted third molar. [Methods:] Among the patients with mandibular impacted teeth admitted to our department of stomatology from October 2020 to March 2022, seventy-eight patients were selected and randomly divided into two groups: control group (39 cases) and research group (39 cases) according to the extraction method. The control group took traditional hammer elevator for tooth extraction with high-speed turbines. The research group used the pneumatic tooth elevator with high-speed turbines. The occurrence of surgical indicators (extraction time and socket integrity), the intraoperative evaluation indexes (root fracture, gingival tear, lingual plate fracture, adjacent tooth injury) and the postoperative evaluation indexes (pain level, mouth opening at 72 hours after surgery, facial swelling at 72 hours after surgery) were statistically compared. [Results:] Theextraction time and the integrity of the extraction socket in the research group were significantly better than those in the control group (P<0.05), and the intraoperative and postoperative evaluation indexes in the research group were significantly better than those in the control group (P<0.05). [Conclusion:] The advent of pneumatic tooth extraction elevators in the treatment of mandibular impacted third molar combined with minimally invasive high-speed turbine provides new treatment options for managing patients with impacted third molars.